2023
DOI: 10.1111/jdv.18924
|View full text |Cite
|
Sign up to set email alerts
|

3D Whole‐body skin imaging for automated melanoma detection

Abstract: Background Existing artificial intelligence for melanoma detection has relied on analysing images of lesions of clinical interest, which may lead to missed melanomas. Tools analysing the entire skin surface are lacking. Objectives To determine if melanoma can be distinguished from other skin lesions using data from automated analysis of 3D‐images. Methods Single‐centre, retrospective, observational convenience sample of patients diagnosed with melanoma at a tertiary care cancer hospital. Eligible participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Three articles [35,37,38] reported 3D TBP in clinical settings. Two of these studies [35,37] had small participant numbers, ranging from n = 6 to 10 participants with MM and n = 55 to 65 participants with an otherwise benign diagnosis.…”
Section: Assessment Of Performance Metrics 3d Tbpmentioning
confidence: 99%
See 1 more Smart Citation
“…Three articles [35,37,38] reported 3D TBP in clinical settings. Two of these studies [35,37] had small participant numbers, ranging from n = 6 to 10 participants with MM and n = 55 to 65 participants with an otherwise benign diagnosis.…”
Section: Assessment Of Performance Metrics 3d Tbpmentioning
confidence: 99%
“…Of these two studies, one study [37] reported an AUROC value of 0.92. One study [38] followed a different methodology and did not report values for sensitivity, specificity and accuracy. However, the AUROC was reported (0.9399) and was included (Table 2).…”
Section: Assessment Of Performance Metrics 3d Tbpmentioning
confidence: 99%
“…Several papers of this issue highlight new and established technologies to improve medical care. [3][4][5][6] Still, we are all aware that certain grey zones will remain.…”
Section: Melanoma Is Not Just One Disease But Manymentioning
confidence: 99%
“…Fundamental for achieving treatment precision is diagnostic accuracy. Several papers of this issue highlight new and established technologies to improve medical care 3–6 . Still, we are all aware that certain grey zones will remain.…”
mentioning
confidence: 99%
“…To date, a limited number of AI models in dermatology have been applied to TBP or wide-field photography ( 12 , 13 ). TBP for skin cancer monitoring provides the advantage of objectively capturing the entire skin surface and ability to compare sequential images between appointments.…”
Section: Introductionmentioning
confidence: 99%